High Expression of sLex Associated with Poor Survival in Argentinian Colorectal Cancer Patients. Issue 1 (January 2014) - Zwenger, Ariel; Rabassa, Martin; Demichelis, Sandra; Grossman, Gabriel; Segal-Eiras, Amada; Croce, Maria Virginia
Aim: Colorectal cancer (CRC) is one of the most prevalent malignancies in Argentina with 11, 043 new cases and 6, 596 deaths estimated to have occurred in 2008. The present study was developed to clarify the differential expression of MUC1, MUC2, sLex, and sLea in colorectal cancer patients and their relationship with survival and clinical and histological features. Methods: Ninety primary tumor samples and 43 metastatic lymph nodes from CRC patients were studied; follow-up was documented. Twenty-six adenoma and 68 histological normal mucosa specimens were analyzed. An immunohistochemical approach was applied and statistical analysis was performed. Results: In tumor samples, MUC1, sLea, and sLex were highly expressed (94%, 67%, and 91%, respectively); also, we found a significantly increased expression of the 3 antigens in primary tumors and metastatic lymph nodes compared with normal mucosa and adenomas. MUC2 was expressed in 52% of both normal mucosa and CRC samples; this reactivity significantly decreased in metastatic lymph nodes (p<0.05). A multiple comparison analysis showed that MUC1 and sLex discriminated among 3 groups: normal, adenoma, and CRC tissues. The increase of sLex expression showed an association with recurrence, and survival analysis showed that a high sLex staining was significantly associated with a poor survival. By multivariate analysis MUC1 inmunoreactivity correlated positively and significantly with tumor size, while MUC2 expression showed the opposite correlation. Conclusions: The correlation of sLex overexpression in primary tumors and metastatic lymph nodes, the discrimination among the normal, adenoma, and CRC groups based on sLex expression, as well as its association with recurrence and survival, all suggest a prognostic role of sLex in Argentinian CRC patients.